Determination of Sugar Content in Fruit Juices Using High Performance Liquid Chromatography - Sophi Damayanti; Benny Permana; Choong Chie Weng (School of Pharmacy Institut Teknologi Bandung, 2012)
Sugar is a sweet, water-soluble, crystallizable material which is obtained commercially from sugarcane or sugar beet. As an important source of dietary carbohydrate, a sweetener, preservative in foods and a cause factor for Diabetic disease, analysis of sugar content is needed. The objective of this study was to verify the suitability and determination of sugar content in fruit juices using HPLC. The fresh fruits except strawberries were peeled, cut and blended using homogenizer. After filtration, 12.5mL of each fresh juices and packed juices were diluted with acetonitrile and distilled water (50:50). The diluted fresh juices and packed juices were loaded onto C18 Sep-Pak cartridge. Fructose, glucose, and sucrose of each fresh juices and packed juices were analyzed in HPLC with Refractive Index detector, NH2 polar bonded phase column, 10Î¼m (250mm Ã—4.6mm I.D.), temperature of 43.5°C, mobile phase of acetonitrile and 10mM sodium phosphate (monobasic) (78:22) and flow rate of 1.0mL/min. The method validation showed good linearity of equations for fructose, glucose and sucrose were y = 3833208.4806x